Implementation of Parallel Programming in One-Dimensional Electromagnetic Simulation with the FDTD Method - Edmond Febrinicko Armay; Heni Rachmawati (Jurnal Komputer Terapan, 2022)
Simulation of electromagnetic in 1D has been done using FDTD method. The simulation is conducted on some scenario, starting from one-dimensional free space, absorbing boundary condition in one dimension, propagation in a dielectric medium, simulating different sources, and propagation in a lossy dielectric medium. To accelerate calculation process, parallel programming technique is used on looping parts of simulation.